Assessing the accuracy and teachers' impressions of Google Translate: A study of primary L2 writers in Hong Kong. (October 2019) - Stapleton, Paul; Leung Ka Kin, Becky
Highlights: Primary 6 students wrote on the same topic in English and their native Chinese. The Chinese scripts were translated into English using Google Translate (GT). 12 teachers (without knowing about GT) graded the two sets of scripts. The GT-translated scripts were graded equal or higher. Teachers were interviewed for their impressions of GT.